A134 ANALYSIS OF POTENTIAL MICROBIAL-METABOLITE SENSORS IN THE BRAIN DURING EXPERIMENTAL COLITIS - Vicentini, F (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Patients with inflammatory bowel disease frequently show changes in behavior. Known as sickness behaviors, these alterations include anxiety, depression, fatigue and social withdrawal. The pathways by which inflammation in the gut leads to changes in the brain are yet to be fully elucidated. Recently it has been shown that the enteric microbiota plays a significant role in gut-brain communication. During gut inflammation, the microbiota are altered, possibly modifying the interactions established between bacterial metabolites and the brain. These changes could be related to the onset of the sickness behaviors. Furthermore, receptors in the brain that might sense the microbial metabolites are poorly described. AIMS: To investigate the presence of potential microbial-metabolite receptors in the brain: Pregnane X receptor (PXR), aryl hydrocarbon receptor (AhR), toll-like receptor 4 (TLR4), free-fatty acid receptor 2 and 3 (FFAR2 and FFAR3) - and their potential modulation during colonic inflammation. METHODS: Colitis was induced in male C57Bl/6 mice by administration of 2.5% dextran sulphate sodium (DSS) in the drinking water for 5 days. Controls were housed in the same room and received normal drinking water. On day 7, macroscopic damage of the colon was assessed and the brain was collected: sagittally divided in half, or by dissecting the hypothalamus, hippocampus, and amygdala. Bacterial receptors were assessed by RT-qPCR. RESULTS: DSS-treated mice presented with body weight loss (p=0.002) and increased macroscopic damage score (p<0.0001) compared to controls. Half brains from control mice were used to evaluate the presence of the receptors. AhR and TLR4 mRNA expression was found in half brain samples (Ct value < 30), whilst the PXR, FFAR2, and FFAR3 had low mRNA expression under baseline conditions (Ct value > 30). The expression of AhR and TLR4 in half brain samples was comparable between control and DSS-treated groups (p=0.79 for both receptors). The effect of DSS-induced colitis on AhR mRNA expression in the hippocampus, hypothalamus, and amygdala was examined. There was no effect of colitis on AhR receptor expression, though there was a trend for a reduction in the amygdala (p=0.06) compared to control. To evaluate the activation of AhR, we measured the expression of Cyp1a1 – an up-regulated AhR gene. Colitis did not alter Cyp1a1 mRNA expression in hippocampus, hypothalamus or amygdala. CONCLUSIONS: Some types of microbial-metabolite receptor are present in the brain. Their expression levels appear unaffected by colitis. Further studies are required to identify if the activation of these receptors is a factor in the development of sickness behaviors in colitis. FUNDING AGENCIES: CIHRNational Counsel of Technological and Scientific Development (CNPq – Brazil)